Non-coding RNAs in chromatin disease involving neurological defects - Della Ragione, Floriana; Gagliardi, Miriam; D'Esposito, Maurizio; Matarazzo, Maria R. (Frontiers in Cellular Neuroscience, 2014)
Novel classes of small and long non-coding RNAs (ncRNAs) are increasingly becoming apparent, being engaged in diverse structural, functional and regulatory activities. They take part in target gene silencing, play roles in transcriptional, post-transcriptional and epigenetic processes, such as chromatin remodeling, nuclear reorganization with the formation of silent compartments and fine-tuning of gene recruitment into them. Among their functions, non-coding RNAs are thought to act either as guide or scaffold for epigenetic modifiers that write, erase and read the epigenetic signature over the genome. Studies on human disorders caused by defects in epigenetic modifiers and involving neurological phenotypes highlight the disruption of diverse classes of non-coding RNAs. Noteworthy, these molecules mediate a wide spectrum of neuronal functions, including brain development, and synaptic plasticity. These findings imply a significant contribution of ncRNAs in pathophysiology of the aforesaid diseases and provide new concepts for potential therapeutic applications.